2015
DOI: 10.1016/j.resmic.2015.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of Clostridium tetani

Abstract: Genomic information about Clostridium tetani, the causative agent of the tetanus disease, is scarce. The genome of strain E88, a strain used in vaccine production, was sequenced about 10 years ago. One additional genome (strain 12124569) has recently been released. Here we report three new genomes of C. tetani and describe major differences among all five C. tetani genomes. They all harbor tetanus-toxin-encoding plasmids that contain highly conserved genes for TeNT (tetanus toxin), TetR (transcriptional regula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 9 publications
0
28
0
Order By: Relevance
“…TeNT is always mentioned and discussed as a single toxin, at variance from the many BoNTs. But this is no longer appropriate as novel TeNT isoforms with slight, but significant, amino acid sequence changes are reported (Alam, Dixit, Tomar, & Singh, ; Bruggemann et al, ; Cohen, Wang, Shen, Wu, & Keller, ; Dixit, Alam, & Singh, ), and surely many more will be found as the sequence of more C. tetani TeNT encoding plasmids become available.…”
Section: Tetanus Neurotoxinsmentioning
confidence: 99%
“…TeNT is always mentioned and discussed as a single toxin, at variance from the many BoNTs. But this is no longer appropriate as novel TeNT isoforms with slight, but significant, amino acid sequence changes are reported (Alam, Dixit, Tomar, & Singh, ; Bruggemann et al, ; Cohen, Wang, Shen, Wu, & Keller, ; Dixit, Alam, & Singh, ), and surely many more will be found as the sequence of more C. tetani TeNT encoding plasmids become available.…”
Section: Tetanus Neurotoxinsmentioning
confidence: 99%
“…This study also suggested that stx expression, and thus virulence, may correlate with the genetic structure of the stx sequence context and the presence of a particular Q antiterminator protein variant [293]. Comparative genomewide analysis, including protein toxin-encoding mobile elements, has been performed in order to gain insights into microepidemiology and evolution of toxin variants [95,99,264,265,[294][295][296].…”
Section: Hgt and The Evolution Of Toxin Familiesmentioning
confidence: 94%
“…The Clostridium tetani structural gene tent encoding the tetanus neurotoxin (TeNT) is located on a 74-kb plasmid such as pE88 [93][94][95][96]. Five tetanus toxin-encoding plasmids have been sequenced.…”
Section: Gram-positive Bacteriamentioning
confidence: 99%
See 1 more Smart Citation
“…BoNTs have sustained numerous genetic rearrangements (mutations, duplication, recombination), resulting in multiple BoNT types and subtypes, whereas only a unique TeNT sequence has been reported until now. Similarly, the genome background of BoNT-producing clostridia is extremely diverse, and only restricted genetic diversity is observed in C. tetani strains (see [5,6,20,21]).…”
Section: Editorialmentioning
confidence: 99%